English Question or Union Question? Neither has Easy Answers. Issue 1 (28th January 2015) - Hazell, Robert; Sandford, Mark
Abstract While devolution has provided a stronger political voice for Scotland, Wales and Northern Ireland since the late 1990s, it is only in the past few years that English public opinion appears to have become exercised by the lack of similar arrangements for England. The renewed debates over the character of the Union after the Scottish independence referendum reveal a desire for 'fair treatment' of England within a Union conceived as a partnership of equals. At the same time, numerous proposals have been made for devolution of power within England, reflecting long‐held concerns about the territorial hegemony of London. Solutions to the former issue include English votes for English laws and an English Parliament. Solutions to the latter include city‐regions, strengthened local government, the first of these appears to be the government's preferred route, in the light of the recent 'Greater Manchester Agreement'. However, none of these 'solutions' can count on being implemented.